The culture of consumption. Issue 1 (1st December 2019) - White, Christine
AbstractThe creative and cultural arts sector in the United Kingdom, most often termed the 'arts and cultural industries' in 2011 had a turnover of £12.4 billion published in Create Arts Council England. The Centre for Economic and Business Research (CEBR) stated that the arts and cultural industry in 2016 was responsible for £21.2 billion direct turnover, which involved 137, 250 jobs. This sector pays 5% more than the UK median salary and so makes a positive contribution to an average household. This industry also plays an important role in supporting wider commercial activity. This includes tourism spend estimated as £856 million and this includes film production advertising, design and crafts all of which is also showcased overseas. In addition, this sector's work is seen to have a wider benefit for health and wellbeing. For example, those who attended a cultural place or event in the preceding twelve months were 60% more likely to report good health and in terms of spend, people valued being in an audience for the arts as they spent £2000 a year on events, which is more than for sport, as cited in the Arts Council England report of 2014. The continued need for reports and advocacy for the value of the arts and how that value should be ascribed is frustrating as there is a continued and pervasive sense that these areas are still of less value when compared with STEM learning and industrial activity, yet there are an estimated 89, 000 jobs in museums, galleries and libraries and 296, 000 jobs in music, performing and visual arts. In 2018, the number of jobs in the creative industries sector stood at just over two million, an increase of 1.6% from 2017. The sector accounted for 6.2% of UK jobs in 2018. The number of jobs in the creative industries has increased by 30.6% from 2011: three times the growth rate of employment in the United Kingdom overall (10.1%) (Department for Digital, Culture, Media and Sport [DCMS] 2018). The cultural sector had a workforce of 659, 000, a fall of 2.1% from 674, 000 in 2017 (a record number). The sector accounted for 2.0% of all UK jobs in 2018. Since 2011, the cultural sector workforce has grown by 21.0%.All of these sectors do not include tourism; however, we know that when people are tourists, they are doing and seeing stuff which is most often in the realm of cultural and creative sector developed activity. Across Europe and by their different methodologies of definition of the cultural sector, defined anyone employed in an economic sector defined as 'cultural', irrespective of whether they are employed in a cultural occupation and all persons with occupations relating to culture are included, even if the people concerned are employed in non-cultural sectors ‐ the number is 8.7 million people (European Union Labour Force Survey: EU-LFS).